1997
DOI: 10.1210/jcem.82.11.4373
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Tumor-Node-Metastasis (pTNM) Staging for Papillary and Follicular Thyroid Carcinomas: A Retrospective Analysis of 700 Patients

Abstract: The TNM classification (tumor-node-metastasis) was adopted by the American Joint Committee on Cancer and the International Union against Cancer a decade ago to avoid heterogeneity of prognostic classification schemes used for differentiated thyroid cancers. To date, however, clinical data based on this classification are lacking. We retrospectively evaluate the prognosis of 700 patients (208 men and 492 women) with papillary (89%) and follicular (11%) thyroid cancers according to the pathological TNM (pTNM) st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 274 publications
(50 citation statements)
references
References 23 publications
3
43
1
Order By: Relevance
“…The incidence of PTC has increased dramatically in the past decades [2], and Chen et al demonstrated that the increasing rate of PTC resulted from an actual increase in disease incidence rather than improvements in the diagnosis such as by high-resolution ultrasound [3]. PTCs, especially papillary thyroid microcarcinomas, tend to have a good prognosis; however, even for TNM stage I patients, approximately 15 % of patients experienced recurrence during 10 years of follow-up in one previous study [4]. Therefore, the classification and targeted therapies for PTC still need more investigation.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of PTC has increased dramatically in the past decades [2], and Chen et al demonstrated that the increasing rate of PTC resulted from an actual increase in disease incidence rather than improvements in the diagnosis such as by high-resolution ultrasound [3]. PTCs, especially papillary thyroid microcarcinomas, tend to have a good prognosis; however, even for TNM stage I patients, approximately 15 % of patients experienced recurrence during 10 years of follow-up in one previous study [4]. Therefore, the classification and targeted therapies for PTC still need more investigation.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Approximately 20% of PTCs demonstrate tumor recurrence, and some reach advanced stages. 6 Various clinicopathological variables, such as tall-cell variant, advanced stage, vascular invasion and nodal or distant metastasis, are related to aggressive behavior of PTC. 7,8 However, the mechanisms underlying the aggressive behavior of some of the papillary thyroid carcinomas resulting in recurrence and metastases are not fully elucidated.…”
mentioning
confidence: 99%
“…Patient information, including demographic data (age and sex), tumor size, cellular characteristics (mitosis or necrosis), nuclear features, extrathyroidal extension, nodal status, distant metastases, and disease stage, were obtained by independent chart review (pathological tumor, node, metastasis [pTNM] staging). 36 Three expert pathologists (M.P., L.L., and S.C.) confirmed the histological classification of the tissues.…”
Section: Histological Examinationmentioning
confidence: 84%